FAKTOR–FAKTOR YANG MEMPENGARUHI AUDIT DELAY DAN DAMPAKNYA TERHADAP AUDITOR SWITCHING (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2012-2015) - Flourencia Claudia Kristiawan, 13.05.52.0033; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2017)
The purpose of this research was to determine the effect firm size profit and loss, audit opinion, and size of public accounting firm to the auditor delay and its impact on the auditor switching. This research uses explanatory study, the research describes the relationship between variables. The type or types of relationships in this study is a causal link between one or more variables. Samples were taken by using purposive sampling technique. Samples were 34 companies from 130 companies listed in Indonesia Stock Exchange in 2012-2015, so that the research data was analyzed totaled 136. To analyze the hypothesis used multiple linier regression and logistic regresion analysis. The results indicate that Audit opinion and profit and loss showed negative and significant effect on audit delay. firm size and size of the public accounting firm not showed effect on audit delay. Audit delay showed positive effect on auditor switching.Keywords: Auditor Switching, Audit Delay, Firm Size, Profit and Loss, Audit Opinion and Size of The Public Accounting Firm